Effect of Fermentation Process on Ashgourd Juice - C.S. Devaki; K.S. Premavalli (Journal of Pharmacy and Nutrition Sciences, 2014)
Ashgourd (Benincasa hispida) is valued for its nutritive and medicinal properties and further value addition is being attempted by fermentation process. In the present study, effect of fermentation was studied by using ashgourd as a substrate for nutrients and flavour components formation. Ashgourd fermented beverage was developed by using commercially available wet yeast and the changes in vitamins profile and flavouring compounds were evaluated after the fermentation process and it was compared with the raw ashgourd juice. Fermentation showed positive response indicating that, thiamine, riboflavin, niacin, pyridoxine and vitamin C were increased by 76µg, 7µg, 171µg, 459µg and 1.5mg respectively per 100 ml of the beverage in comparison to fresh juice. Fermentation showed many flavour components development in comparison to raw ashgourd juice and the fermentation process had a positive response on volatile component formation. Therefore fermentation improved the formation of nutritional and flavour components.